Mucosal Barrier and Th2 Immune Responses Are Enhanced by Dietary Inulin in Pigs Infected With Trichuris suis - Myhill, Laura J.; Stolzenbach, Sophie; Hansen, Tina V. A.; Skovgaard, Kerstin; Stensvold, C. Rune; Andersen, Lee O'Brien; Nejsum, Peter; Mejer, Helena; Thamsborg, Stig M.; Williams, Andrew R. (Frontiers in Immunology, 2018)
Diet composition may play a crucial role in shaping host immune responses and commensal gut microbiota populations. Functional foods,Bioactive dietary components, such as inulin, have been extensively studied for their bioactive properties, particularly in modulating gut immune function and reducing inflammation. Recent reports have suggestedIt has been shown that colonization with gastrointestinal parasitic worms (helminths) may alleviate chronic inflammation through promotion of T-helper cell type (Th) 2 and T-regulatory immune responses and alterations in the gut microbiome. In this study, we investigated if dietary inulin could modulate mucosal immune function in pigs during colonization with the porcine whipwormhelminth Trichuris suis. T. suis infection induced a typical Th2-biased immune response characterised by transcriptional changes in Th2- and barrier function-related genes, accompanied by intestinal remodelling through increased epithelial goblet and tuft cell proliferation. We observed that inulin also up-regulated Th2-related immune genes (IL13, IL5), and suppressed Th1-related pro-inflammatory genes (IFNG, IL1A, IL8) in the colon. Notably, inulin augmented the T. suis-induced responses with increased transcription of key Th2 and mucosal barrier genes (e.g. IL13, TFF3), and synergistically suppressed pro-inflammatory genes such as IFNG and CXCL9. 16S rRNA sequencing of proximal colon digesta samples revealed that inulin supplementation reduced the abundance of bacterial phyla linked to inflammation, such as Proteobacteria and Firmicutes, and simultaneously increased Actinobacteria and Bacteroidetes. Interestingly, pigs treated with both inulin and T. suis displayed the highest Bacteroidetes: Firmicutes ratio and the lowest gut pH, suggesting an interaction of diet and helminth infection that stimulates the growth of beneficial, probiotic bacterial species. Overall, our data demonstrate that T. suis infection and inulin co-operatively enhance anti-inflammatory immune responses, which is potentially mediated by changes in microbiota composition. Our results highlight the intricate interactions between diet, immune function and microbiota composition in a porcine helminth infection model. This porcine model should facilitate further investigations into the use of bioactive diets as immunomodulatory mediators against inflammatory conditions, and how diet and parasites may influence gut health.